Design and performance analysis of wireless body area networks in complex indoor e-Health hospital environments for patient remote monitoring - Erik Aguirre; Peio Lopez-Iturri; Leyre Azpilicueta; Carmen Rivarés; José Javier Astrain; Jesús Villadangos; Francisco Falcone (International Journal of Distributed Sensor Networks)
In this article, the design and performance analysis of wireless body area network–based systems for the transmission of medical information readable in an android-based application deployed within complex indoor e-Health scenarios is presented. The scenario under analysis is an emergency room area, where a patient is being monitored remotely with the aid of wearable wireless sensors placed at different body locations. Due to the advent of Internet of Things, in the near future a cloud of a vast number of wireless devices will be operating at the same time, potentially interfering one another. Ensuring good performance of the deployed wireless networks in this kind of environment is mandatory and obtaining accurate radio propagation estimations by means of a computationally efficient algorithm is a key issue. For that purpose, an in-house three-dimensional ray launching algorithm is employed, which provides radio frequency power distribution values, power delay profiles, and delay spread values for the complete volume of complex indoor scenarios. Using this information together with signal-to-noise estimations and link budget calculations, the most suitable wireless body area network technology for this context is chosen. Additionally, an in-house developed human body model has been developed in order to model the impact of the presence of monitored patients. A campaign of measurements has been carried out in order to validate the obtained simulation results. Both the measurements and simulation results illustrate the strong influence of the presented scenario on the overall performance of the wireless body area networks: losses due to material absorption and the strong influence of multipath components due to the great number of obstacles and the presence of persons make the use of the presented method very useful. Finally, an android-based application for the monitoring of patients is presented and tested within the emergency room scenario, providing a flexible solution to increase interactivity in health service provision.